Cash Flow Moderation between Profitability, Liquidity, and Leverage on Company Value on the Indonesia Stock Exchange - Partogian Sormin (Proceeding of International Conference on Global Innovation and Trend in Economics, 2022)
This study objective is to test the effect of profitability, liquidity, and leverage on firm value where cash flow is treated as a moderating variable. The object of research is the consumer goods industry listed on IDX for the period 2027-2021 by implementing multiple regression analysis models. The results showed that profitability had a positive effect on firm value, while liquidity and leverage had no significant effect on firm value. Meanwhile, cash flow is able to strengthen the influence of profitability on firm value, while variable cash flow is not able to moderate the effect of liquidity and leverage on firm value.